1984
DOI: 10.2134/agronj1984.00021962007600060029x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Selected Tropical Pasture Legumes in Peninsular Florida1

Abstract: The potential N contribution of tropical legumes to grass pastures on the infertile soils of Peninsular Florida necessitates increased efforts to develop suitable pasture legumes. Nineteen accessions representing 17 tropical legume species were evaluated for persistence under grazing in bahiagrass swards on a Peninsular Florida Arenic Haplaquod (Spodosol) soil. After three growing seasons in the mixed grass‐legume swards, only Vigna parkeri Bak. and aeschynomene (Aeschynomene americana L.) covered larger areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although southern crabgrass has been suggested as high quality forage for summer use (Dalrymple et al, 1991), it is often considered an aggressive weed of old world origin (Diggs et al, 1999). This and other grasses are major impediments to establishment and early productivity of warm‐season legumes whose small seed and slow seedling development do not make them competitive with grasses in the southeastern USA (Pitman and Kretschmer, 1984) unless these grasses are suppressed (Thro and Shock, 1987).…”
mentioning
confidence: 99%
“…Although southern crabgrass has been suggested as high quality forage for summer use (Dalrymple et al, 1991), it is often considered an aggressive weed of old world origin (Diggs et al, 1999). This and other grasses are major impediments to establishment and early productivity of warm‐season legumes whose small seed and slow seedling development do not make them competitive with grasses in the southeastern USA (Pitman and Kretschmer, 1984) unless these grasses are suppressed (Thro and Shock, 1987).…”
mentioning
confidence: 99%
“…gumes in bahiagrass (Paspalum notatum Flugge) pastures under grazing has shown that even those adapted to the edaphic and climatic conditions of peninsular Florida flatwoods generally fail to survive the com-. bination of grass competition and livestock grazing (Pitman and Kretschmer, 1984;Pitman et al, 1988).…”
mentioning
confidence: 99%
“…Only a few individual plants of the shrub, D. virgatus, have survived the establishment period in germplasm screening trials (Pitman and Kretschmer, 1984) at Ona, Florida, due in part to defoliation by deer ( Odocoileus virginian us semina/us Goldman and Kellogg) and rabbits (Sylvilagus spp.). Plants which have survived the establishment period have persisted for several years under periodic grazing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In peninsular Florida very little of this information is available on tropical forage legumes. Pitman and Kretschmer (1984) have conducted initial work with a number of introduced legumes at the Ona Agricultural Research and Education Center (Ona AREC) encompassing 19 accessions from 17 species as well as 50 entries in a further work (Pitman et al, 1988).…”
mentioning
confidence: 99%